Risk of needing completion thyroidectomy for low‐risk papillary thyroid cancers treated by lobectomy. Issue 3 (6th February 2019) - DiMarco, A. N.; Wong, M. S.; Jayasekara, J.; Cole‐Clark, D.; Aniss, A.; Glover, A. R.; Delbridge, L. W.; Sywak, M. S.; Sidhu, S. B.
Abstract : Background: Low‐risk differentiated thyroid cancers may, according to the American Thyroid Association (ATA) 2015 guidelines, be managed initially with lobectomy. However, definitive risk categorization requires pathological assessment of the specimen, resulting in completion thyroidectomy being recommended when discordance between preoperative and postoperative staging occurs. This study sought to establish the expected rate of completion thyroidectomy in patients with papillary thyroid cancer (PTC) treated by lobectomy. Methods: Patients with PTC treated over 5 years (2013–2017 inclusive) and meeting the ATA criteria for lobectomy were identified from the prospectively developed database of a high‐volume, university department of endocrine surgery. Concordance between the ATA initial and final recommendation, and the putative rate of completion thyroidectomy were calculated. Multivariable analysis was used to assess preoperative factors as predictors of the need for total thyroidectomy. Results: Of 275 patients with PTC who met ATA preoperative criteria for lobectomy there was concordance between this and the final recommendation in 158 (57·5 per cent) and discordance in 117 (43·5 per cent). Most common reasons for discordance were: angioinvasion (30·8 per cent), local invasion (23·9 per cent) or both (20·5 per cent). Four patients (1·5 per cent) had permanent hypoparathyroidism. On multivariable analysis, age, sex, tumour size and family history did not independently predict the final treatment required. Conclusion: Although many patients may be treated adequately with lobectomy, just under half would require completion thyroidectomy. Further work is needed on preoperative risk stratification but, before this, total thyroidectomy remains the treatment of choice for low‐risk 1–4‐cm PTC in the hands of high‐volume thyroid surgeons who can demonstrate low complication rates. Abstract : The American Thyroid Association guidelines of 2015 suggest hemithyroidectomy for low‐risk 1–4‐cm papillary thyroid cancers (PTCs). However, the final management is dependent on histology. This retrospective analysis established that, if managed with hemithyroidectomy, 42·5 per cent of patients would go on to require completion thyroidectomy. Actual management was total thyroidectomy in 98·0 per cent, with complications in only 1·5 per cent. Given the high rate of completion surgery predicted, the authors will continue to recommend total thyroidectomy as initial management of low‐risk 1–4‐cm PTC. Existing guidance needs revision